Delivery systems for simultaneous intake of probiotics and plant extracts - Silva, Marluci Palazzolli da (2021)
The association of plant extracts and probiotics is promising for simultaneous delivery of functional compounds in the gut, providing numerous benefits to the host. This study presented as overall aims (i) to assess the prebiotic potential and antioxidant activity of guaraná extracts; (ii) to co-encapsulate probiotics and guaraná extracts by complex coacervation and evaluate the stability and release in simulated gastrointestinal fluids (SGF); (iii) to incorporate microcapsules loaded simultaneously with probiotic and guaraná seed extract (GSE) and the same ingredients in free form in yogurt drink; (iv) to elaborate peanut butter containing free and co-encapsulated probiotic and guraná peel extract (GPE); (v) to evaluate strains with probiotic potential as carries for vacuum biosorption of plant extracts and evaluate the protection of phenolic compounds, probiotic viability, and release of phenolics in SGF; (vi) to verify the survivability of probiotic cell loaded with plant extracts in SGF. GSE and GPE showed antioxidant and prebiotic potential. In this way, co-encapsulation improved the survival of probiotics in simulated gastrointestinal fluids and during storage. In addition, approximately 60% of phenolic compounds from GSE were released into the gastric fluid. In contrast, the carotenoids present in GPE were gradually released, reaching an accumulative release rate of 90% after the addition of simulated intestinal fluid. Regarding the production of functional yogurt, the microcapsules simultaneously loaded with probiotics and GSE masked the bitter taste and avoided post-acidification of the product. Peanut butter protected both free and encapsulated probiotics, and the product added with free GPE showed lower acceptance by the tasters. In the final stage of this study, a novel technique based on vacuum biosorption was evaluated to bind phenolic compounds from jabuticaba peel extract (JPE) and GSE into potential probiotic strains. Although probiotic cells loaded between 5 to 9 mg Gallic Acid Equivalent - GAE/g, which were values significantly lower than those found in microparticles, the biosorption of plant extracts in probiotics increased the hydrophobicity of the cells by at least 3-fold. Furthermore, the release of phenolic compounds bound in cells ranged between 55% and 75% in simulated gastrointestinal fluids, while the counts of probiotics loaded with plant extracts were maintained. Overall, microencapsulation by complex coacervation allowed the delivery of probiotics and bioactive compounds from guaraná extracts to develop fortified yogurt drink and peanut butter, maintaining the quality and sensory parameters of these products. Vacuum biosorption is a promising technology for delivering viable probiotics loaded with JPE and GSE in the gut, excluding the need to use biopolymers to protect the probiotics.